EVALUATION OF SOME BIOCHEMICAL PARAMETER ON CHRONIC RENAL FAILURE BEFORE AND AFTER INFECTION WITH SARS-COV-2 - Haba Muatasim Bakr BAKR; Assoc. prof. Dr. Sevki ADEM; Prof. Dr. Sabah Hussian KORSHEED (Scholar Express Journals, 2023)
In the current investigation, the researchers wanted to determine the levels of liver enzyme activity, renal function, and other biochemical parameters in CKD patients who either had or did not have COVID19 infection. At Azadi Teaching Hospital and Al-Jumhuri Hospital, it was stated that a total of one hundred patients were infected with CKD and with or without COVID-19 between the months of December 2022 and January 2023. The investigation was carried out at independent research facilities located in Kirkuk, Iraq. The results showed that the kidney functions of CKD patients, urea and creatinine levels were significantly (P< 0.05) higher in patients without COVID and in patients with COVID when compared to the control group. Concerning the levels of liver enzymes in CKD patients, AST, ALT, and LDH levels exhibited non-significant (P< 0.05) differences in comparison to the control group when comparing patients with COVID and patients without COVID. For electrolytes, S. calcium levels exhibited a significant (P <0.05) decrease in patients who did not have COVID as well as those who had COVID when compared to the control group. When compared to the control group, patients who did not have COVID and patients who did have COVID had significantly higher levels of zinc and phosphorus in their serum (P><0.05). When compared to the control group, patients without COVID and patients with COVID both revealed substantial (P><0.05) decreases in their vitamin D concentrations>
Keywords: liver enzymes; COVID-19; chronic renal disease